PERAN PENDIDIKAN VOKASI DALAM PEMBANGUNAN EKONOMI - PH., Slamet (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: The Contribution of Vocational Education to Economic Development. One of the challenges lying ahead is how to improve the contribution of vocational education to economic development. Several studies confirm that such contribution is very significant. In the current practices of vocational education, however, there is still a mismatch among quantitative, qualitative, location, and time requirements that stem from the world of work. The world of work requires that vocational education produce graduates that are in line with those four requirements. Efforts to maximize the contribution of vocational education to economic development can be undertaken by offering vocational education based on Indonesian characteristics, strengthening link and match with the world of work, integrating soft skills into learning, and implementing entrepreneurship education (small scale enterprise education). Keywords : vocational education, economic development, link and match, soft skills, and entrepreneurship